Real-Time Implementation of CLMS Algorithm in 3P4W Solar PV-BES-Based Microgrid System - Narayanan, Vivek; Kewat, Seema; Singh, Bhim (IEEE transactions on industry applications, 2021)
A solar photovoltaic (PV)-battery energy storage (BES) involved the microgrid (MG) system is presented in this article. It contains a bidirectional dc-dc converter (BDDC), which is responsible for extracting the maximum power output from the PV array by regulating the dc-link voltage to the maximum power point (MPP) voltage of the PV array. Whenever the PV array is not delivering any power, then the control of the BDDC is automatically shifted to regulate the dc-link voltage to a constant dc voltage. Thus, the BDDC regulates the dc-link voltage to the desired voltage in the presence of BES in the MG. Whenever the BES is disconnected from the MG, then the voltage source converter (VSC) regulates the dc-link voltage to the desired value. Thus, it enhances the reliability of the system. The neutral current compensation is performed by the zig-zag transformer, which is connected at the load end. The VSC performs different functions such as mitigation of harmonics and reactive power, balancing of grid currents, and the regulation of the dc-link voltage in the absence of BES. The system behavior is analyzed under different operating conditions in the simulation platform and in the laboratory conditions on a prototype.